Answer:
The solution is: x = -1, and y = 8/3
Explanation:
Notice that the system of equations can be easily solved via the "elimination" method, by subtracting term by term one equation from the other. Doing such will remove completely the term in "y" (since the terms in "y" are exactly equal in both equations), and leave only an equation containing "x", for which the value can be solved:
![2x+3y=6\\-4x+3y=12\\\\ \\2x-(-4x)+3y-(3y)=6-12\\6x+0=-6\\x=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/6c1bw0zi6kebruq4o8wcsn4jp1qmrvmeoi.png)
Now we use this x-value in either equation to solve for y: